A game theoretical approach to road safety - Pål Andreas Pedersen (University of Kent, Department of Economics, 2001)
A theoretical model is adopted in order to explain incentives and actual safety behaviour for drivers, pedestrians and other road users which do not utilise motorised vehicles. A road user's outcome is supposed to be dependent on her individual actions and cares decided upon by other individuals utilising the roads simultaneously, as well as on external traffic safety conditions. By varying the types of road users meeting in traffic and the order of moves taken, several different games are identified, analysed and compared. In addition to focussing on the possible strategic interactions between the road users and the outcomes most likely to be found in different situations, we discuss the existence and size of moral hazard effects caused by improvements in external safety conditions.
Keywords: R4; C7; D8; 330; Road safety; strategic interaction; moral hazard; Straßenverkehrssicherheit; Moral Hazard; Spieltheorie; Theorie